Review on the biosynthesis of anthocyanidins and proanthocyanidins in rice and their impact on rice quality - ZHOU Yufeng; XIE Huifang; SUN Yuxuan; JIANG Shuo; WU Dianxing; SHU Xiaoli (浙江大学学报. 农业与生命科学版)
Anthocyanidins and proanthocyanidins have important health benefits for the human body. Anthocyanidins are present mainly as glycosylated or acetylated anthocyanins in nature, and proanthocyanidins exist in the form of polymers, with a wide variety of types and antioxidant properties. Pigmented rice, especially black rice, contains abundant anthocyanidins and proanthocyanidins, and it is becoming favorable. Here, we reviewed the research progress on anthocyanidins and proanthocyanidins in rice, emphasizing their molecular genetic mechanisms, isolation, purification, and detection methods, as well as their effects on starch physicochemical and digestive properties. Furthermore, we proposed several perspectives for future studies on pigmented rice, providing alternative considerations for further development, utilization and breeding of pigmented rice.